Drug-drug Interactions between COVID-19 Treatments and Antidepressants, Mood Stabilizers/Anticonvulsants, and Benzodiazepines: Integrated Evidence from 3 Databases - Plasencia-García, Beatriz Oda; Rico-Rangel, María Isabel; Rodríguez-Menéndez, Gonzalo; Rubio-García, Ana; Torelló-Iserte, Jaime; Crespo-Facorro, Benedicto (Pharmacopsychiatry, 2021)
Introduction The SARS-CoV-2 pandemic with psychiatric comorbidities leads to a scenario in which the use of psychotropic drugs may be required. This requires the support of evidence-based medicine to take into account possible interactions between antidepressants, mood stabilizers, benzodiazepines, and coronavirus infection treatments.Methods Three databases were consulted: (a) Lexicomp Drug Interactions, (b) Micromedex Solutions Drugs Interactions, (c)Liverpool Drug Interaction Group for COVID-19 therapies. The CredibleMeds QTDrugs List was also queried. Hydroxychloroquine, chloroquine, azithromycin, lopinavir-ritonavir, remdesivir, favipiravir, tocilizumab, baricitinib, anakinra, and dexamethasone – drugs used for SARS-CoV-2 – were analyzed, and consensus recommendations are made.Results The potential interactions of agomelatine, desvenlafaxine, duloxetine, milnacipran, and vortioxetine with COVID-19 treatments shall be considered less risky. Antidepressant interactions with hydroxychloroquine, chloroquine, and azithromycin enhance the risk of QT prolongation, and ECG monitoring is advised for most antidepressants. Antidepressants with lopinavir/ritonavir involve multiple CYP enzyme interactions (except with milnacipran). Gabapentin, oxcarbazepine, pregabalin, topiramate, and zonisamide are safe treatment options that have no significant interactions with COVID-19 treatments. Lithium is contraindicated with hydroxychloroquine, chloroquine, and azithromycin. Precaution should be taken in using valproic acid with lopinavir-ritonavir. The use of benzodiazepines does not present a risk of drug interaction with COVID-19 treatments, except lopinavir/ritonavir.Conclusions Clinicians prescribing antidepressants, mood stabilizers/anticonvulsants, and benzodiazepines, should be aware of the probable risk of drug-drug interaction with COVID-19 medications and may benefit from heeding these recommendations for use to ensure patient safety.
Keywords: antidepressants; anticonvulsants; lithium; benzodiazepines; SARS-CoV-2 infection; coronavirus disease 2019; mental health